Pencapaian perundingan & pencapaian penyelidikan 2018 / Ainorkhilah Mahmood - Mahmood, Ainorkhilah (Jabatan Sains Gunaan, 2019)
*Program Bumiputera Cemerlang Sains (PBCS) Kohort VI *Program Bumiputera Cemerlang Sains (PBCS) Kohort V *Effect of Frequency Response in AC Electrophoretic deposition for fabrication of MWCNTs - PANi Nanocomposite Thin Film. *Chemical Management and Safety in Small and Medium Printing Enterprise in Pulau Pinang. *Properties and Growth Mechanism of Novel Integrated Pulsed Electrochemical Etching of Porous GaN for Potential Optoelectronics Application.